An evaluation of the technical efficiency of cultural institutions in Poland: a case study of the regional system of public libraries - Suchecki, Adam M. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
The political transformation of 1989, as well as Poland’s accession to the European Union in 2004, had a significant impact on the cultural sector and the forms of its organisation and funding. These events also contributed to setting new directions for Polish cultural policy. This is a part of a wider public policy, understood as an intentional and deliberate process of achieving objectives in particular areas of public life. Currently, the library policy is an integral component of Polish cultural policy. It aims to achieve specific objectives and implement tasks in the field of the social circulation of library books and the preservation of the linguistic, cultural and civilisational heritage for future generations. Since 2001, public spending on culture in Poland has remained below 1% of the total expenditures of the state budget. The limited financial resources earmarked for culture in the national and provincial budgets are the main reasons for performing a comparative study of the technical efficiency of cultural institutions in Poland using the example of libraries. The Polish system of public libraries consists of national, educational, school, medical, agricultural, prison and military libraries. The operations of these institutions require adequate funding to guarantee meeting society’s reading and informational needs. The main aim of this paper is to gauge the efficiency of the regional system of libraries in Poland. The research focuses on analysing the public libraries operating in Polish provinces, using data from Polish Statistical Office resources (The Local Database), and one of the nonparametric methods, i.e. the results-oriented CCR model of data envelopment analysis (DEA). It was found that the major reason for the lack of efficiency in most Polish libraries is the insufficient amount of local government’s financial support combined with the lack of self-financing opportunities for such cultural institutions
Argumenta Oeconomica, 2020, Nr 2 (45), s. 163-187
Keywords: culture; cultural economics; data envelopment analysis; libraries; public policy; efficiency